2014
DOI: 10.1002/ejlt.201300278
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic oil uptake mechanisms in fried products*

Abstract: The increasingly poor perception of fried products encourages the development of rupture technologies to reduce oil uptake. The current available descriptions of oil uptake mechanisms remain incomplete, neglecting: (i) the critical role of the total pressure gradient inside hygroscopic materials during cooling, (ii) the coupling between mechanical ruptures and oil uptake routes, (iii) the different configurations of biphasic oil-air flow inside the material: co-and counter-currents. This paper demonstrates how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 67 publications
2
41
0
2
Order By: Relevance
“…It allows distinguishing between air-filled pores and the solid parts of the fry and thus visualization of the crust morphology. In a recent study Vauvre, Kesteloot, Patsioura, and Vitrac (2014) already used XRT to image the structure of the crust. However, the development of structure was not studied as function of the frying conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It allows distinguishing between air-filled pores and the solid parts of the fry and thus visualization of the crust morphology. In a recent study Vauvre, Kesteloot, Patsioura, and Vitrac (2014) already used XRT to image the structure of the crust. However, the development of structure was not studied as function of the frying conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Slow freezing produces big size crystal, which damages the cell [7,16]. Then it could increase oil penetration, since oil could penetrate into damaged cell during the frying [72]. Thus, fast freezing is preferred to minimize oil uptake.…”
Section: Freezingmentioning
confidence: 99%
“…Potato slices with different pore diameters could also alter water evaporation behavior, which affected equilibrium TO content and oil absorption during frying. Vauvre et al 21 reported that an average potato cell diameter was about 200 μm, so the bigger the pore, the more damaged the cells. When potato slices were immersed in hot oil, water released selectively through defects and open channels 27 .…”
Section: To Content During Frying Processingmentioning
confidence: 99%
“…Based on these, we attempted to exploit the effect of pore size on oil absorption of fried samples. The operation of pre-drying and simulation system may lead to irregularity, uncontrollable and broad range of pore size and the gradient of connectivity, which were complicated in the interpretation of the dynamics of oil uptake and increased the difficulty of study 21 . Based on this, the puncture experiment with different pore diameters was used to obtain uniform and controllable pores in fresh potato slices and the effect of initial pore diameter on oil absorption was investigated.…”
Section: Introductionmentioning
confidence: 99%